Oral care as a life course project: A qualitative grounded theory study. (19th September 2018) - Gibson, Barry J.; Kettle, Jennifer E.; Robinson, Peter G.; Walls, Angus; Warren, Lorna
Abstract : Objective: To report on a theory to explain the oral health of older people over the life course. Background: The study of ageing has burgeoned into a complex interdisciplinary field of research, yet there are few studies in oral health from the perspective of older people that bridge the gap between sociology and oral health related research. Methods: A grounded theory study involving a convenience sample of 15 men and 28 women aged between 65 and 91 years across different levels of education. Data were subjected to grounded theory analysis using QSR NVivo 11.0 and where relevant phenomenological theory. Results: Participants conceived of oral care as a life course project that resulted from an active plan to keep one's teeth into older age. This involved accessing the social world of dentistry, holding appropriate values, understanding the associated personality types, social practices, goals and outcomes. The life course project is a social project supported by social institutions. It involves ideas about appropriate ageing including how oral health is to be managed at different stages in the life course. The degree to which individuals are able to participate in this project is determined by both individual and social factors. Conclusions: The theory explains why the loss of a single tooth might be experienced as traumatic but also why older people adapt to their changing oral health. Oral health in older age represented a lifetime's investment in oral care. Future health policies should consider this lifetime investment when considering care for older people.